Bell’s Palsy - Ruslan Ramlan Ramli; Stanley Sesar Tjahjadi (Universitas Muhammadiyah Palu, 2023)
Bell's Palsy is defined as acute facial nerve paralysis affecting one side, with unknown causes. The cause of Bell's Palsy itself is upper respiratory tract viral infection, inflammation, autoimmune and ischemic. However, if no specific cause can be identified, this condition is known as bell's palsy which is caused by inflammation or nerve damage. Often the eye on the affected side cannot be closed, the nasolabial folds and forehead lines disappear. Corticosteroids have been found to improve Bell's palsy when used early, while anti-viral drugs have not shown many signs of improvement 10 days after onset, even without treatment. This article aims to review Bell's Palsy, especially its pathophysiology. The level of severity determines the healing process for Bell's Palsy.